Groundwater vulnerability assessment of nitrate pollution in the Ankang Basin: using an optimized DRASTIC-LY method - Tian Hui; Xiao Changlai; Xu Honggen; Liang Xiujuan; Qian Jianli; Qiao Longtan; Zhang Weilong; Zhang Hong (IWA Publishing, 2023)
This study retains the basic structure of DRASTIC model and obtains more specific evaluation results by adding land-use type and groundwater resource yield parameters, modifying the rating scale and weight of nine parameters. Comparison of the modified DRASTIC-LY vulnerability map with the map of the original DRASTIC-LY method revealed differences in 40.49% of the study area. The risk map shows that the very high vulnerability area decreased from 2.79 to 1.67%, while the high vulnerability area increased from 18.70 to 28.86%. Areas with low vulnerability increased by 10.15%, while areas with medium vulnerability decreased by 15.01%. The areas with very high groundwater vulnerability are mainly distributed in the Hanbin area on the north bank of the Han River, the areas with high are mainly concentrated on both sides of the Fujia River, while the areas with low are distributed in most areas in the west of the basin. The Pearson's correlation factor was 0.0583 in the original DRASTIC model, 0.1113 in the DRASTIC-LY method and 0.8291 in the modified DRASTIC-LY model, which indicated that the revised DRASTIC-LY model was more appropriate than the original model. The results can help the government with the protection of water resources. HIGHLIGHTS Improve the DRASTIC model.; Determine the weight, grade and category of each parameter.; Based on the sensitivity analysis and model validation results, construct the best model suitable for groundwater vulnerability assessment.; The results of this study will help government managers improve the composition of water use and strengthen the protection of vulnerable aquifers.;